A study on the effects of service quality dimension towards customer retention in Hotel Hallmark Leisure, Melaka / Siti Nor Azimah Abdul Rahman - Abdul Rahman, Siti Nor Azimah (2012)
The purpose of this research is to measure the importance of the service quality dimensions own by Hotel Hallmark Leisure towards customer retention. As information, the service quality dimensions are the instrument used by the customers as well as the service provider in evaluating the service quality provided by the organisation. There are basically five dimensions of the service quality dimensions which are tangibles, reliability, responsiveness, assurance and empathy. The main objective of this research is to identify how effective the service quality dimensions is being used in Hotel Hallmark Leisure in order to retain the customers. In addition, this research is also conducted to provide several recommendations and suggestions to improve the service quality of Hotel Hallmark Leisure. This research is conducted by using probability sampling which 100 random sample of respondent has been chosen to answer a questionnaire to gain the feedback regarding the organisation and the service quality provided. All of the respondents chosen are the quest of the Hotel Hallmark Leisure itself in order to ensure the accuracy of the data received. The Statistical Package for Social Science (SPSS) version 20 had been used to analyze and summarize the data. The results of the findings show that Hotel Hallmark Leisure has provided the best service quality to the customers but still lacking in several aspects. Therefore, several recommendations and suggestions are made to overcome the problems arise.